Lessons from Mahatma Gandhi for Today’s School Principals: An Instructional Model - Obaki, Samuel O.; Sang, Anthony; Ogenga, Paul (ABC Journal of Advanced Research, 2013)
This article presents Mahatma Gandhi’s leadership styles, ethical principles, and practices that school principals and those aspiring to become school administrators should learn and apply in their schools. The model intends to reinforce the principals’ understanding the value of applying some of Gandhi’s leadership styles in Kenyan schools. This theoretical research was based on the existing literature on Gandhi’s leadership in India and principals’ leadership including their principles and practices in Kenya. The study found that good leadership in this technologically changing world needs a principal who is innovative, supportive, knowledgeable, people-oriented and skilled in matters related to curriculum implementation. It was further found that good principals initiate, empower, and create good relationships with faculty and other school community members in order to transform their schools.